A.R. Fakhruddin Wajah Tasawuf dalam Muhammadiyah - Masyitoh Masyitoh (Millah: Journal of Religious Studies, 2008)
With emphasizing to truth Islam and refusal to taqlid, bid'ah and churafat, Muhammadiah has appreciation to Islamic mysticism (read: akhlaki Islamic mysticism). Although Islamic mysticism is more individual necessity and the term has never been mentioned, but many of Muhammadiyah figures practice Islamic mysticism individually. It was began from founder of Muhammadiyah, KH. Ahmad Dahlan and other figures, such as: Ki Bagus Hadikusumo, KH. Mas Mansyur, Buya Hamka, AR Fakhruddin, etc. A.R Fakhruddin him self can be addressed as Kadda an yukuuna Suufiyan (near to be a Sufi), in this case Sufi Akhlaqi. It is caursed by all akhlakul karimah characteristics have already mixed up in his soul, such as: patient, thank God, Wara Zuhud, Qana'ah, Tawakkal, Ikhlas, Risha, etc. In the meantime, his spiritual life which fills more of his life and it is reflecting Islamic mysticism attitudes. A Sufi's live can be reflected from his attitude and thought about: taubat, taqarrub, dzikrullah, khusyu', tawaddhu', khauf, raja, muraqobah, and istiqamah, these maqam are common to be done in Islamic mysticism world.  Muhammadfyah, mysticism, Sufi Akhlaqi, Spiritual and maqam.